PERILAKU MAHASISWA ILMU PERPUSTAKAAN UIN SUNAN KALIJAGA YOGYAKARTA DALAM MENYIKAPI HOAKS DI MEDIA SOSIAL - Silmi Afkarina Hanum; Anis Masruri (Fihris: Jurnal Ilmu Perpustakaan dan Informasi, 2021)
This study aims to determine the behavioral stages of students in responding to hoaxes, which are increasingly rampant due to the easy access to information that is widely available on social media so that there is no information filtering system when information is disseminated on social media. Social media is a virtual social place between individuals, to share information with each other. The subjects of this study were students major of library science, faculty of civil and cultural science State Islamic University of Sunan Kalijaga Yogyakarta. The Major of Library Science has contributed to the development of information literacy in Indonesia. Information literacy consists of searching, analyzing and finding the information needed. This research uses descriptive qualitative research methods. Techniques for determining informants using purposive sampling or non-random techniques. There are 16 students of the Library Science study program who are included in the category of research informants. The research method was carried out by interview and documentation. Researchers gave several questions to informants regarding information and hoaxes circulating on social media. Then the informants analyzed the information on social media, and distinguished valid and hoax information. The results showed that the behavioral stages of Library Science students at UIN Sunan Kalijaga Yogyakarta in responding to hoax information on social media were 1. Students searched for news on social media, 2. Students looked at posted news accounts / sources, 3. Students paid attention to synchronization of titles and contents. news, 4. Students check the validity of the news by means of; a. see the comments column, b. double check, and c. crosscheck.